Transcriptome Profiling of Huanglongbing (HLB) Tolerant and Susceptible Citrus Plants Reveals the Role of Basal Resistance in HLB Tolerance - Wang, Yunsheng; Zhou, Lijuan; Yu, Xiaoyue; Stover, Ed; Luo, Feng; Duan, Yongping (Frontiers in Plant Science, 2016)
Huanglongbing (HLB) is currently the most destructive disease of citrus worldwide. Although there is no immune cultivar, field tolerance to HLB within citrus and citrus relatives has been observed at the USDA Picos farm at Ft. Pierce, Florida, where plants have been exposed to a very high level of HLB pressure since 2006. In this study, we used RNA-Seq to evaluate expression differences between two closely related cultivars after HLB infection: HLB-tolerant ‘Jackson’ grapefruit-like-hybrid trees and HLB susceptible ‘Marsh’ grapefruit trees. A total of 686 genes were differentially expressed (DE) between the two cultivars. Among them, 247 genes were up-expressed and 439 were down-expressed in tolerant citrus trees. We also identified a total of 619 genes with significant differential expression of alternative splicing isoforms between HLB tolerant and HLB susceptible citrus trees. We analyzed the functional categories of DE genes using two methods, and revealed that multiple pathways have been suppressed or activated in HLB tolerant citrus tree, which lead to the activation of the basal resistance or immunity of citrus plants. We have experimentally verified the expressions of 14 up-expressed genes and 19 down-expressed genes on HLB-tolerant ‘Jackson’ trees and HLB-susceptible ‘Marsh’ trees using real time PCR. The results showed that the expression of most genes was in agreement with the RNA-Seq results. This study provided new insights into HLB-tolerance and useful guidance for breeding HLB-tolerant citrus in the future.